The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10964-012-9801-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support in Students’ Perceived Abilities and Attitudes Toward Math and Science

Abstract: Social cognitive models examining academic and career outcomes emphasize constructs such as attitude, interest, and self-efficacy as key factors affecting students' pursuit of STEM (science, technology, engineering and math) courses and careers. The current research examines another under-researched component of social cognitive models: social support, and the relationship between this component and attitude and self-efficacy in math and science. A large cross-sectional design was used gathering data from 1,55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
126
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 36 publications
10
126
1
11
Order By: Relevance
“…Thus, strengthening children's agency might constitute an avenue to reducing educational inequalities among children of diverse social origins. For instance, the degree of social support experienced by children can influence children's attitudes and perceptions of their academic abilities (Rice et al 2013), suggesting that social support may increase their sense of competence and, thus, agency. However, to effectively improve children's agency in the domain of schooling, we believe that a better empirical understanding of child agency in educational stratification and mobility is important because as long as researchers and policymakers fail to recognize that children from all social classes possess capacities that are instrumental in coping with challenges in education, they run the risk of maintaining a "patronizing view of the very people whom they seem dedicated to 'liberating'" (Côté 2002, p. 132).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, strengthening children's agency might constitute an avenue to reducing educational inequalities among children of diverse social origins. For instance, the degree of social support experienced by children can influence children's attitudes and perceptions of their academic abilities (Rice et al 2013), suggesting that social support may increase their sense of competence and, thus, agency. However, to effectively improve children's agency in the domain of schooling, we believe that a better empirical understanding of child agency in educational stratification and mobility is important because as long as researchers and policymakers fail to recognize that children from all social classes possess capacities that are instrumental in coping with challenges in education, they run the risk of maintaining a "patronizing view of the very people whom they seem dedicated to 'liberating'" (Côté 2002, p. 132).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Indonesia, the report of Program International Student Assessment (PISA) in 2012 , showed that the achievement scores of Indonesian students in mathematics are recorded very low to 375 which is below the OECD average of 494, and was ranked the 64th out of 65 countries. Rice, Barth, Guadagno, Smith, & McCallum (2013) reported that the interest of students to the Science, Technology, Engineering and Mathematics (STEM) is very low due to three factors, i.e. : students' attitude towards STEM, students' perception on their ability to STEM, and social support on the development of abilities and careers in STEM.…”
mentioning
confidence: 99%
“…: students' attitude towards STEM, students' perception on their ability to STEM, and social support on the development of abilities and careers in STEM. In comparison to other subject, students tend to be negative towards STEM (Rice et al, 2013;Goodykoontz, 2008), and perceptions of their ability in mathematics are closely linked to mathematics achievement (de Backer & Nelson, 2000;Rice et al, 2013). The study of Veloo, Noor, and Khalid (2015), reported that the relationship between students' attitude towards Physics and achievement in Physics was positively significant.…”
mentioning
confidence: 99%
“…Based on the existing gender gaps in the STEM field it may be possible that self-efficacy for males and females varies. According to Rice, Barth, Guadagno, Smith, and McCallum (2013), self-efficacy for girls remains stable or decreases and self-efficacy for boys tends to decrease throughout adolescence. Support from parents, teachers and peers can affect a student's self-efficacy in science and math.…”
Section: Math and Science Self-efficacy And Postsecondary Education Pmentioning
confidence: 99%